PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 016 BULUH KASAP - Asmah Asmah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study is a classroom action research, which aims to improve the learning outcomes of math students class IISD Negeri 016 Buluh Kasap. This research is based on low student learning outcomes, from 25 students the totalnumber of students who completed is 11 students (44.00%) with an average value of 54.28. On this basisresearchers apply direct learning models to improve student learning outcomes. The result of research indicatethat the result of student learning have improvement in every cycle in cycle I increase with total student which iscomplete is 16 student (64,00%). And on the second cycle increased to 21 students (84.00%). In addition, theaverage student learning outcomes experienced an increase in the cycle I average student score increased withthe acquisition of 68.76. And on the second cycle the average value of students increases with an averagestudent score of 75.68.